Thermal Behavior of Novel Aromatic Oligoesters and Oligoesteramides - Deberdeev, T.R.; Akhmetshina, A.I.; Karimova, L.K.; Grishin, S.V.; Kochemasova, D.V. (KU Publ., 2022)
Liquid crystalline polymers, depending on their structure and macromolecular architecture, are found in a number of commercial applications, ranging from state-of-the-art engineering plastics to soft matter artificial muscles and microrobots. Rigid chain liquid crystalline polymers are known as indispensable materials for high technology industries. However, their relatively high costs provoke the search for novel cost-effective mesogenic monomers. In this regard, a series of aromatic oligoesters and oligoesteramides were synthesized via high-temperature polycondensation of aromatic dicarboxylic acids with 4-hydroxybenzoic acid (or 4-aminobenzoic acid) and 1,5-naphthalene diol. The structure of the synthesized compounds was identified using FTIR spectra analysis. According to polarizing microscopy observations, novel oligoester based on 4-hydroxybenzoic acid, 1,5-naptalene diol and terephthalic acid demonstrated liquid crystallinity with nematic texture, whereas other samples occurred in amorphous state in case of oligoester or in crystalline state in case of oligoesteramides. A relatively wide range of mesophase existence from 120 to 290 °C was found for the thermotropic oligoester using differential scanning calorimetry. While aromatic oligoesters at the beginning of the degradation processes were highly stable towards heat with comparable values of Т10, which were equal to 372–378 °C, aromatic oligoesteramides started to decompose at the temperatures lower by more than 50 °C than those for oligoesters.
Жаңа ароматты олигоэфирлер мен олиготерамидтердің жылулық қасиеттері
Термические свойства новых ароматических олигоэфиров и олигоэфирамидов
Keywords: liquid crystalline polymers; phase transitions; polarizing microscopy; thermal stability; solubility; high-temperature polycondensation